2016
DOI: 10.1186/s12879-016-1684-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and characteristic of virulence gene of community-acquired and hospital-acquired methicillin-resistant Staphylococcus aureus isolates in Sun Yat-sen Memorial hospital, Guangzhou, Southern China

Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of both hospital and community infections globally. It's important to illuminate the differences between community-acquired MRSA (CA-MRSA) and hospital-acquired MRSA (HA-MRSA), but there have been confusions on the definition, especially for the MRSA isolates identified within 48 h of admission. This study aimed to determine the molecular characteristics and virulence genes profile of CA and HA-MRSA isolates identified less than 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
37
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 34 publications
(40 reference statements)
10
37
3
Order By: Relevance
“…MRSA rates were lower in males than in females. This is in agreement with studies conducted in Iraq (Assafi et al, 2015) and China (Xie et al, 2016), and in contrast to a study performed in Nepal (Ansari et al, 2016). In addition, the data from the present study revealed that age had no influence on the MRSA nasal colonization rate among local participants and Syrian refugees.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…MRSA rates were lower in males than in females. This is in agreement with studies conducted in Iraq (Assafi et al, 2015) and China (Xie et al, 2016), and in contrast to a study performed in Nepal (Ansari et al, 2016). In addition, the data from the present study revealed that age had no influence on the MRSA nasal colonization rate among local participants and Syrian refugees.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the data from the present study revealed that age had no influence on the MRSA nasal colonization rate among local participants and Syrian refugees. Similar results have been reported from studies in China (Lin et al, 2016;Xie et al, 2016) and Nepal (Ansari et al, 2016). Moreover, it was observed that the number of family members showed no association with nasal carriage colonization of MRSA.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of CA-MRSA SSTIs was reported to be 57% in the US in 2004 [12], but there was no report of such infections in mainland China before 2009. A few studies reported that CA-MRSA accounted for 4.0% of community-acquired S. aureus SSTIs in Beijing (northern China, isolates collected from children between 2008 and 2009), 3.4% in Guangzhou (southern China, 2006-2011, adults and children) and 10.3% in Wuhan (central China, 2011-2013, adults and children) [13][14][15]. Likewise a multicentre study (2009-2011, adults and children) found a low prevalence of CA-MRSA SSTIs ranging from 1.3% in northern China to 6.1% in southwestern China, and 3.8% in a children's hospital in Shanghai [16].…”
Section: Discussionmentioning
confidence: 99%
“…Invasive MRSA infection has been identified as an independent risk factor for poor prognosis and is associated with a significant increase in the duration of hospitalization (8,9). Although MRSA-ST239-SCCmec III represents the most common clone in China, others are also in circulation, whose antimicrobial resistance profiles differ (10). Thus, the provision of data concerning antibiotic resistance is important to enable clinicians to choose appropriate treatments.…”
Section: Introductionmentioning
confidence: 99%